A comparative retrospective study on the prevalence and therapeutic treatment of dental agenesis between healthy children and children with systemic disease or congenital malformation - Nadolinski, Mirja; Schlenz, Maximiliane Amelie; Rahman, Alexander; Krämer, Norbert; Schulz-Weidner, Nelly; Justus Liebig University Giessen (My University, 2023)
Background: Dental agenesis (DA) in the permanent dentition is one of the most common dental anomalies, with a prevalence up to 2–10%. Therefore, the aim of this retrospective study was to investigate the prevalence and therapeutic treatment of DA in healthy children (HC) compared to children with systemic disease or congenital malformation (SD/CM). Methods: Out of 3407 patients treated at the Department of Paediatric Dentistry of the Justus Liebig University Giessen (Germany) between January 2015 and December 2020, a total of 1067 patients (594 female, 473 male) aged between 4.5 and 18 years were included in this study due to DA. Besides the patients’ general medical history and therapeutic treatments, panoramic radiographs were analysed. Results: In contrast to the HC group with 9.7% DA, the SD/CM group showed a significantly higher prevalence of DA (19.8%; p < 0.05). The latter group was further classified into children with ectodermal dysplasia (4.4%), down syndrome (8.2%), cleft lip and palate (4.4%), intellectual disability/developmental delay (16.4%), and other genetic/organic diseases without intellectual disability (45.9%). Regarding therapeutic treatments, the HC group (59.5%) was significantly more often treated with an orthodontic gap opening compared to the SD/CM group (42.6%; p < 0.05), followed by orthodontic gap closing 36.5% in the HC group and 22.9% in the SD/CM group (p < 0.05), whereas no treatment was predominantly performed in the SD/CM group (37.7%) compared to the HC group (4%; p < 0.05). Furthermore, 50% in the SD/CM group required general anaesthesia for therapeutic treatment (vs. 8.1% in the HC group; p < 0.05). Conclusions: Children with SD/CM suffered more often from DA compared to HC that underlines multi- and interdisciplinary treatment of utmost importance. Furthermore, due to intellectual disability, common treatment methods can be complicated by insufficient compliance. This fact underlines the importance of an early attempt to establish the necessary cooperation enabling children with SD/CM to receive therapy.
Keywords: ddc:610